Hypokalemia Induced Ventricular Arrhythmia In Heart Failure Patient With Complete Revascularization: A Case Report - Rochmawati, Icmi Dian; Rizal, Ardian; Rohman, Mohammad Saifur; Prasetya, Indra (Heart Science Journal, 2023)
BackgroundSudden mortality due to persistent VT or VF accounted for around half of all fatalities in these high-risk individuals. Myocardial ischemia, acute heart failure, electrolyte abnormalities, hypoxia, and drug-related arrhythmogenicity are all risk factors for electrical storms. The most common electrolyte imbalance is hypokalemia.Case illustration:A 54-year-old man was readmitted to ER with palpitations and chest pain. The patient's heart rate was recorded as sinus bradycardia however, shortly the patient developed ventricular tachycardia of approximately 300 beats per minute (bpm) and unstable. Although multiple synchronized cardioversion dosage was administered, the VT reoccurred again. Complete revascularization was demonstrated at his most recent catheterization three months ago. His potassium in the serum was 2.88 mmol/L and corrected with drip KCl. The patient's potassium levels were then normalized stable for the remainder of their hospital stay.ConclusionCareful medication reconciliation is critical for avoiding the potentially fatal cardiovascular effects of severe hypokalemia. Patients with CHF are more likely to have life-threatening hypokalemia and ventricular arrhythmias. The phenotypic expression of ventricular tachycardia in HF results from alterations in neurohormonal signaling, structural remodeling, and electrophysiology.